Cancer Survivors Awaiting Rehabilitation Rarely Meet Recommended Physical Activity Levels: An Observational Study. Issue 4 (October 2018) - Dennett, Amy M.; Peiris, Casey L.; Shields, Nora; Prendergast, Luke A.; Taylor, Nicholas F.
Abstract : Objective: We aimed to describe physical activity levels and identify factors associated with physical activity of cancer survivors awaiting oncology rehabilitation. Methods: A pilot observational study evaluating physical activity levels of 49 cancer survivors referred to outpatient rehabilitation was assessed using accelerometers worn continuously for 6 days. Multiple linear regression analyses were completed to identify factors associated with physical activity. Variables included demographic factors (cancer type, treatment, body mass index), physical factors (walking capacity, physical performance), and psychological factors (anxiety). Results: Four participants achieved recommended physical activity levels. Participants recorded an average of 12 minutes (SD = 12) of daily moderate-intensity activity. Walking capacity had the strongest independent association with physical activity ( P < .001). A 10-m increase in distance in the 6-Minute Walk Test was associated with a 7% improvement in physical activity. Breast cancer diagnosis ( P = .005), increased anxiety ( P = .007), and lower body mass index ( P = .014) were also independently associated with high physical activity. The final model explained 70.5% of the variance in physical activity levels ( P ⩽ .001). Conclusion: Few cancer survivors awaiting rehabilitation achieve recommended physical activity levels. Factors associated with low levels of physical activity such as reduced walking capacity may be modified by oncology rehabilitation.